2021
DOI: 10.1098/rsos.211121
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of joint commitment in great apes' natural joint actions

Abstract: Human joint action seems special, as it is grounded in joint commitment—a sense of mutual obligation participants feel towards each other. Comparative research with humans and non-human great apes has typically investigated joint commitment by experimentally interrupting joint actions to study subjects’ resumption strategies. However, such experimental interruptions are human-induced, and thus the question remains of how great apes naturally handle interruptions. Here, we focus on naturally occurring interrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 74 publications
3
22
1
Order By: Relevance
“…One aspect currently missing from the picture is partner behaviour: while within-player behaviour shows limited predictability, it might be more predictable when knowing what the partner did. Chimpanzees and other primates engage in turn-taking when communicating ( Chow, Mitchell & Miller, 2015 ; Fröhlich, 2017 ), and play has been described as a context that elicits joint commitment between players, with clear evidence that they re-establish that commitment after breaks ( Heesen et al, 2021a ; Heesen et al, 2021b ). Thus, we need an approach that understands social interactions (including play) as a complex system of decisions taken by all involved individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One aspect currently missing from the picture is partner behaviour: while within-player behaviour shows limited predictability, it might be more predictable when knowing what the partner did. Chimpanzees and other primates engage in turn-taking when communicating ( Chow, Mitchell & Miller, 2015 ; Fröhlich, 2017 ), and play has been described as a context that elicits joint commitment between players, with clear evidence that they re-establish that commitment after breaks ( Heesen et al, 2021a ; Heesen et al, 2021b ). Thus, we need an approach that understands social interactions (including play) as a complex system of decisions taken by all involved individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we need an approach that understands social interactions (including play) as a complex system of decisions taken by all involved individuals. Importantly, we do not currently know the effect of rule violations on play bouts—play is frequently suspended ( Heesen et al, 2021b ) and facial expressions are used to extend play in situations that might otherwise be interpreted as agonistic ( Palagi et al, 2016 ; Waller & Dunbar, 2005 ), but whether these are preceded by inappropriate responses from play partners is not currently known. One question is whether play is indeed more complex in its sequential structure than other social contexts, such as grooming or aggressions, or communicative exchanges, especially when we include the constraints afforded by the play context—for example, playing in trees removes the possibility to slap the ground.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] argue that the feeling of mutual obligation intrinsic to joint commitment (the product ) is not always formulated explicitly, but can emerge from a gradual, coordinated process of (not necessarily conventional) signal exchanges during joint action. Given that experts, including philosophers, agree that neither promises nor agreements are needed to establish a joint commitment, it becomes plausible that nonhuman primates and possibly other species might engage in joint commitments, something for which there is now some preliminary evidence in bonobos and chimpanzees [ 23 , 27 , 28 ]. The authors show that commitments always vary in strength, are affected by prior actions, depend on stacking and persistence, need to be reinstated after interruptions, and go beyond spoken language.…”
Section: Revisiting the Interaction Engine: Nearly Two Decades Latermentioning
confidence: 99%
“…Beyond vocalizations, recent work on how great apes get into and out of joint activities [21][22][23] has shown that they can flexibly select gestural signals to communicate a desire to start or end a joint activity such as grooming or playing, or to resume an ongoing activity that has been interrupted. The occurrence of communicative signals is inversely correlated with bondedness (less communication to start and end joint activities between friends), at least in bonobos.…”
Section: Introductionmentioning
confidence: 99%